Surveillance profiles and bio-control of Salmonella in retail food and generation of Salmonella ghosts as inactivated vaccine - Thung, Tze Young (2017)
This study involves the surveillance profiles and bio-control of Salmonella in retail food. A total of 360 samples, beef (n=240) and chicken meat (n=120) were collected from wet market and hypermarket. The most probable number (MPN)-multiplex polymerase chain reaction (PCR) was used for the prevalence and quantification studies. The prevalence of 11.9% (43/360) of Salmonella spp., 3.1% (11/360) of Salmonella Enteritidis and 1.4% (5/360) of Salmonella Typhimurium with estimated quantity varied from <3 to 15 MPN/g had been detected. The fifty nine (n=59) isolates were further tested with antibiotic susceptibility test and they were found to be resistant to at least three out of seventeen antibiotics. In recent years, bacteriophages have been reported as a plausible alternative to antibiotics. A total of 29 bacteriophages were isolated from different types of food (beef, chicken meats, cucumber, lettuce, clam, cockles and shrimp). Bacteriophage SE07 was selected for further characterization. The morphology of SE07 indicated that it belong to the Podoviridae family. SE07 was found to demonstrate a broader host range in which it was able to infect Salmonella London, London, London, London, London, London, London, London, Salmonella Newport and Newport and Newport and Newport and Newport and Newport and Newport and Newport and Newport and Salmonella Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Weltevreden, apart from Salmonella Enteritidis the original host. The optimal multiplicity of infection (MOI) was 0.1. SE07 has a latent period of 75 min and generated a burst size of 58 particles per infective center. It demonstrated a broader spectrum of pH tolerance (pH 4-11) and was stable at the temperatures ranging from 28-65˚C. The effectiveness of bacteriophage SE07 was determined in four different food matrices (fruit juice, fresh eggs, beef and chicken meat) experimentally contaminated with Salmonella Enteritidis. A reduction of bacterial count by 2 log cycles was observed in both liquid and solid food. In order to develop a novel non-living vaccine candidate, Salmonella bacterial ghosts (BGs) were successfully produced by using the constructed lysis plasmid containing the PhiX174 lysis E gene and the thermothermothermothermo-sensitivesensitivesensitivesensitivesensitivesensitivesensitive lamda PR-cI857 promoter.